Citrulline enhances myofibrillar constituents expression of skeletal muscle and induces a switch in muscle energy metabolism in malnourished aged rats. Issue 14 (10th June 2013) - Faure, Cécile; Morio, Béatrice; Chafey, Philippe; Le Plénier, Servane; Noirez, Philippe; Randrianarison‐Huetz, Voahangy; Cynober, Luc; Aussel, Christian; Moinard, Christophe
<x xml:space="preserve">Abstract</x> Citrulline (Cit) actions on muscle metabolism remain unclear. Those latter were investigated using a proteomic approach on Tibialis muscles from male Sprague‐Dawley rats. At 23 months of age, rats were either fed ad libitum (AL group) or subjected to dietary restriction for 12 weeks. At the end of the restriction period, one group of rats was euthanized (R group) and two groups were refed for one week with a standard diet supplemented with nonessential amino acids group or Cit (CIT group). Results of the proteomic approach were validated using targeted Western blot analysis and assessment of gene expression of the related genes. Maximal activities of the key enzymes involved in mitochondrial functioning were also determined. Cit supplementation results in a significant increase in the protein expression of the main myofibrillar constituents and of a few enzymes involved in glycogenolysis and glycolysis (CIT vs. AL and R, p < 0.05). Conversely, the expression of oxidative enzymes from Krebs cycle and mitochondrial respiratory chain was significantly decreased (CIT vs. AL, p < 0.05). However, maximal activities of key enzymes of mitochondrial metabolism were not significantly affected, except for complex 1 which presented an increased activity (CIT vs. AL and R, p < 0.05). In conclusion, Cit supplementation increases expression of the main myofibrillar proteins and seems to induce a switch in muscle energy metabolism, from aerobia toward anaerobia.